Additional file 1 of Genomic and resistome analysis of Alcaligenes faecalis strain PGB1 by Nanopore MinION and Illumina Technologies - Jidong Lang; Yanju Li; Wenjuan Yang; Ruyi Dong; Yuebin Liang; Jia Liu; Lanyou Chen; Weiwei Wang; Binbin Ji; Geng Tian; Nanying Che; Bo Meng (figshare, 2022)
Additional file 1.
Keywords: Genetics